Causes and consequences of adaptation to extreme environments - Coffin, John Lodge (Kansas State University, 2022)
Adaptation is ubiquitous in nature, yet our mechanistic understanding of how adaptation occurs and its consequences for populations remains lacking in many natural systems. Extreme environments, characterized by strong physiochemical gradients lethal to most organisms, are ideal systems to investigate the causes of adaptation because selective regimes are well-defined, enabling powerful tests of a priori predictions about how resident populations cope with the harsh conditions. Comparisons of extremophile populations with closely related populations in benign habitats facilitate studies of adaptive divergence between ecotypes, but how adaptive divergence coincides with the evolution of reproductive isolation and a reduction in gene flow (i.e., ecological speciation occurs) remains poorly studied. I begin by reviewing these concepts and synthesizing the overall findings of my dissertation in Chapter 1. To fill knowledge gaps related to the causes and consequences of adaptation, I studied extremophile populations of two species of livebearing fishes, Western mosquitofish (Gambusia affinis) living in a heavy metal polluted stream in Oklahoma, USA and Atlantic mollies (Poecilia mexicana) inhabiting freshwater springs rich in toxic hydrogen sulfide (H₂S) in Tabasco and Chiapas, Mexico. Little is known about how G. affinis survive in heavy metal contaminated environments, so in Chapter 2, I quantified metal accumulation and gene expression differences between populations of G. affinis inhabiting polluted and unpolluted habitats to identify potential mechanisms by which extremophile populations may be able to tolerate and adapt to the toxic environment. I found that G. affinis accumulated heavy metals but may be able to achieve tolerance by detoxifying heavy metals and their toxic intermediates by increasing gene expression of antioxidant genes. However, there was little evidence for adaptive divergence between populations of G. affinis living in contrasting habitats, indicated by a general lack of population differentiation and local adaptation. In contrast, the evidence for adaptation of P. mexicana to H₂S is much clearer, but how divergence between populations interacts with phenotypic plasticity (e.g., through maternal effects) to shape trait variation remains unclear. Therefore, in Chapter 3, I measured phenotypic divergence between H₂S-adapted and non-adapted populations of P. mexicana and determined the relative impacts of genetics and maternal effects on divergence to understand the origins of adaptive trait variation. I found significant functional trait divergence between ecotypes of P. mexicana that was primarily caused by population differences, while plasticity from maternal effects played a relatively weaker role, suggesting divergence is primarily a consequence of local adaptation. Finally, there is also evidence that adaptation to H₂S has coincided with strong— though incomplete—reproductive isolation between sulfidic and nonsulfidic populations of P. mexicana occurring before copulation, but it remains to be tested whether there are any reproductive barriers acting after mating. To begin to understand the nature of reproductive barriers that may arise after copulation, in Chapter 4, I analyzed the strength of isolation occurring between copulation and fertilization (i.e., postcopulatory prezygotic isolation) by characterizing population differences in sperm competitive traits along a gradient of H₂S and in homotypic and heterotypic ovarian fluid. This allowed me to determine whether sperm competition and/or cryptic female choice may contribute to reproductive isolation and speciation. There was little evidence for reproductive isolation occurring due to sperm competition or cryptic female choice, which suggests that processes after fertilization are likely major barriers to gene flow that contribute to speciation. My dissertation provides empirical data to connect the causes (adaptation to habitats with divergent ecological selective regimes) and consequences (the accumulation of differences that leads to reproductive isolation and reduced gene flow) of adaptation in extreme environments, which has important implications for understanding the origins of biodiversity through ecological speciation.
Keywords: Adaptation; Ecological speciation; Extreme environments; Transcriptomics; Maternal effects; Sperm competition